The JN.1 variant of COVID-19: immune evasion, transmissibility, and implications for global health - Araj Naveed Siddiqui; Imshaal Musharaf; Bashar Haruna Gulumbe (Therapeutic Advances in Infectious Disease)
The emergence of the COVID-19 JN.1 variant has raised global health concerns as it gains prevalence in several regions worldwide. First identified in August 2023, JN.1 evolved from the Omicron lineage’s BA.2.86 subvariant. Patients infected with JN.1 commonly exhibit symptoms such as sore throat, fever, dry cough, nausea, and vomiting. While the World Health Organization has labeled JN.1 a Variant of Interest, it currently presents a low global health risk. However, its increased transmissibility, particularly in cold, dry climates, is concerning. This review provides a comprehensive overview of JN.1’s biological characteristics, epidemiology, transmissibility, immune evasion, and the efficacy of existing antiviral treatments and vaccination strategies. A literature search across key databases targeted studies from January 2023 to August 2024, emphasizing recent insights into JN.1’s spread and clinical impact. Findings reveal that JN.1 exhibits higher infectivity and immune evasion than previous variants, largely due to the L4555 mutation. From November 2023 to March 2024, JN.1 showed an increasing trend in transmission. Previously approved antivirals, including Paxlovid, Veklury, and Lagevrio, demonstrate effectiveness against JN.1, and current vaccines still protect against severe illness from this variant. However, vaccination rates remain low. Monitoring efforts include genomic assessments, wastewater surveillance, and digital tracking to contain the variant’s spread. It is essential to encourage the public to maintain vaccination and preventive measures to reduce JN.1’s impact. Continued research is critical for understanding and managing the evolving landscape of COVID-19 and its emerging variants.